Chronic hypoxia reprograms human immature dendritic cells by inducing a proinflammatory phenotype and TREM‐1 expression. Issue 4 (6th March 2013) - Pierobon, Daniele; Bosco, Maria Carla; Blengio, Fabiola; Raggi, Federica; Eva, Alessandra; Filippi, Miriam; Musso, Tiziana; Novelli, Francesco; Cappello, Paola; Varesio, Luigi; Giovarelli, Mirella
<x xml:space="preserve">Abstract</x> DCs are powerful antigen‐presenting cells central in the orchestration of innate and acquired immunity. DC development, migration, and activities are intrinsically linked to the microenvironment. DCs migrate through pathologic tissues before reaching their final destination in the lymph nodes. Hypoxia, a condition of low partial oxygen pressure, is a common feature of many pathologic situations, capable of modifying DC phenotype and functional behavior. We studied human monocyte‐derived immature DCs generated under chronic hypoxic conditions (H‐iDCs). We demonstrate by gene expression profiling the upregulation of a cluster of genes coding for antigen‐presentation, immunoregulatory, and pattern recognition receptors, suggesting a stimulatory role for hypoxia on iDC immunoregulatory functions. In particular, we show that H‐iDCs express triggering receptor expressed on myeloid cells(TREM‐1), a member of the Ig superfamily of immunoreceptors and an amplifier of inflammation. This effect is reversible because H‐iDC reoxygenation results in TREM‐1 down‐modulation. TREM‐1 engagement promotes upregulation of T‐cell costimulatory molecules and homing chemokine receptors, typical of mature DCs, and increases the production of proinflammatory, Th1/Th17‐priming cytokines/chemokines, resulting in increased T‐cell responses. These results suggest that TREM‐1 induction by the hypoxic microenvironment represents a mechanism of regulation of Th1‐cell trafficking and activation by iDCs differentiated at pathologic sites.